PEMODELAN SISTEM INFORMASI PENILAIAN PRESTASI KERJA PEGAWAI KANTOR DINAS KOMUNIKASI DAN INFORMATIKA (DISKOMINFO) KOTA PONTIANAK - Pratama, Eri Bayu; Kadarusman, Kadarusman (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
Employee performance appraisal is a way of evaluating employee work performance with a set of objective benchmarks that are directly related to one's duties and are carried out regularly. Employee performance appraisal is carried out by the Pontianak City Office of Communication and Information with conventional techniques so that the presentation of employee performance reports is not timely, inaccurate and less than optimal. The author intends to conduct research to solve the problems experienced by the Office of Communication and Information Pontianak by designing employee performance appraisal information systems using UML (Unified Modeling Language) modeling consisting of diagrams use cases, class diagrams and sequence diagrams. Data collection techniques are done using descriptive methods to collect data, analyze and interpret it. As well as having a user (actor) who acts as access to manage the information system that will be used, the user (actor) consists of Employees, Section Heads (KASI) and Heads of Offices. Employees can fill in the attendance list every working day. Section Head can process employee data, work target data, integrity and quality data as well as work performance data. The Head of Service can process user data and access employee performance reports.